Onshore catering increases the risk of diarrhoeal illness amongst cruise ship passengers - Pugh, Robyn E; Selvey, Linda; Crome, Mark; Beers, Mary Y (Communicable Diseases Intelligence, 2001)
Of 134 Queensland passengers on a cruise, 91 (67.9%) people reported various illnesses including 41 (30.6%) who reported diarrhoeal symptoms. Queensland passengers who ate while onshore at non-Australian ports were significantly more at risk of developing diarrhoeal symptoms than those who did not. Passengers were particularly at risk when they ate onshore while undertaking a tour compared with those who did not undertake this tour. Travellers should be warned of the possibility of contracting diarrhoeal illness from onshore catering. Commun Dis Intell 2001;25:15-17.